Chitosan-DNA nanoparticles: synthesis and optimization for long-term storage and effective delivery - Aigul Raimbekova; Ulpan Kart; Akbayan Yerishova; Timur Elebessov; Sergey Yegorov; Tri Thanh Pham; Gonzalo Hortelano (PeerJ)
Background Chitosan nanoparticles (CsNPs) are an effective and inexpensive approach for DNA delivery into live cells. However, most CsNP synthesis protocols are not optimized to allow long-term storage of CsNPs without loss of function. Here, we describe a protocol for CsNP synthesis, lyophilization, and sonication, to store CsNPs and maintain transfection efficiency. Methods The size and zeta potential of CsNPs were analyzed by dynamic light scattering (DLS) and the morphology of CsNPs was assessed by transmission electron microscopy (TEM). HEK293 cells were transfected with CsNPs, and expression of H2B-CMV-mScarlet plasmid was assessed by flow cytometry. Confocal microscopy was used to visualize post-transfection gene expression. Time, volume, and effect of sonication were tested to optimize the lyophilization process. Results DLS and TEM analysis indicated amine groups on chitosan to phosphate groups on DNA (N:P) ratios yielded smaller CsNPs sizes. Transfection efficiency, measured by FACS and confocal microscopy, peaked at N:P ratios of 2:1 and 3:1 for both fresh and lyophilized CsNPs. Chitosan/DNA complexes remained stable in solution for at least 72 h at a ratio ≥2:1 as assessed by agarose gel electrophoresis. A lower surface charge with lower N:P ratios was indicated by zeta potential measurements. Lyophilized CsNPs lost 50% transfection efficiency compared to those freshly made. In contrast, sonication of lyophilized CsNPs restored their transfection efficiency to the level of fresh CsNPs. Sonicated CsNPs maintained spherical morphology, while unsonicated CsNPs showed aggregates. Cytotoxicity assays revealed high cell viability (>90%) after CsNPs transfection for a ratio of 2:1 or 3:1. Conclusion This optimized CsNPs synthesis protocol opens the possibility of long-term storage for CsNPs, which would provide broader applications of this technology.